2019
DOI: 10.1111/apha.13299
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of erythrocyte function: Multiple evolutionary solutions for respiratory gas transport and its regulation in fish

Abstract: Gas transport concepts in vertebrates have naturally been formulated based on human blood. However, the first vertebrates were aquatic, and fish and tetrapods diverged hundreds of millions years ago. Water-breathing vertebrates live in an environment with low and variable O 2 levels, making environmental O 2 an important evolutionary selection pressure in fishes, and various features of their gas transport differ from humans. Erythrocyte function in fish is of current interest, because current environmental ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 159 publications
(294 reference statements)
0
27
0
Order By: Relevance
“…As shown in Figure 3 , the cellular processes related to oxygen metabolism and exchange were most involved in the protective effect of STS against cerebral hemorrhage. Hemoglobin and carbonic anhydrase are essential for transportation and exchange of CO 2 and O 2 in red blood cells ( Nikinmaa et al, 2019 ). Carbonic anhydrase accompanied by Na+/H+ exchange regulates intracellular PH ( Parks et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3 , the cellular processes related to oxygen metabolism and exchange were most involved in the protective effect of STS against cerebral hemorrhage. Hemoglobin and carbonic anhydrase are essential for transportation and exchange of CO 2 and O 2 in red blood cells ( Nikinmaa et al, 2019 ). Carbonic anhydrase accompanied by Na+/H+ exchange regulates intracellular PH ( Parks et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of genes of interest, which encode hemoglobin, Na+/H+ exchanger, and carbonic anhydrase, were verified by real-time PCR analysis. Hemoglobin proteins caused dramatic neuronal toxicity in cerebral hemorrhage and regulated the oxygen and carbon dioxide exchange with carbonic anhydrase in blood cells ( Hostettler et al, 2019 ; Nikinmaa et al, 2019 ). We found that the mRNA expression levels of hemoglobin ( hbae1.3, hbae3, hbae5, hbbe2 and hbbe3 ), Na+/H+ exchanger ( slc4a1a and slc9a1 ), and carbonic anhydrase ( cahz ) genes were significantly elevated after cerebral hemorrhage, while STS alleviated the expression changes in of these genes ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differently from mammals, fish RBCs are nucleated cells and have many cytoplasmic organelles, such as mitochondria, Golgi complex, centrioles, ribosomes, microtubules, rough and smooth endoplasmic reticulum (Sekhon & Beams, 1969), and a range of cytoplasmatic enzymes involved in the anaerobic glycolysis (Sephton et al., 1991). These organelles and enzymes allow the functions of RBC to be finely regulated and somewhat independent from other components of the haematopoietic system, enabling fish to occupy a wide range of environments (Nikinmaa et al., 2019). Therefore, species may respond rapidly to changes in oxygen availability (Witeska, 2013), which indicates that it is not constrained by inheritance (Arnold, 1992) or phylogenetic inertia, at least to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from mammals, fish RBC are nucleated cells and have many cytoplasmic organelles, such as mitochondria, Golgi complex, centrioles, ribosomes, microtubules, rough and smooth endoplasmic reticulum (Sekhon and Beams 1969), as well as a range of cytoplasmatic enzymes involved in the anaerobic glycolysis (Sephton et al 1991). These organelles and enzymes allow the functions of RBC to be finely regulated and somewhat independent from other components of the hematopoietic system, enabling fish to occupy a wide range of environments (Nikinmaa et al 2019). Therefore, species may respond rapidly to changes in oxygen availability (Witeska, 2013), which indicates that it is not constrained by inheritance (Arnold 1992) or phylogenetic inertia, at least to a certain degree.…”
Section: Discussionmentioning
confidence: 99%